Industri Kreatif Berbasis Kearifan Lokal: Model Pemberdayaan Majelis Taklim Ponpes Baiturrahman, Madura - Susanto, Dwi; Huda, Lailatul (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
The Ibadurrahman Majelis Taklim at Ponpes Baiturrahman, located in Jaddih Village, Socah District, Bangkalan-Madura, holds significant potential for developing creative industries based on local wisdom. However, the lack of structured mapping and empowerment strategies poses a major challenge to achieving economic independence and prosperity for the taklim congregation. This study employs the Asset-Based Community Development (ABCD) approach, a method of empowerment focusing on identifying, developing, and utilizing the assets or potential of the community. Data were collected through in-depth interviews with village officials, religious leaders (Ponpes Baiturrahman) and members of the taklim majelis to inventory the available assets. The mentoring results received positive feedback and demonstrated an improvement in the ability to map and identify both individual and community assets that could be effectively utilized to manage local potentials, such as craft skills, cultural wisdom and community networks. The empowerment strategies designed included skills training, creative product development and digital-based marketing. In conclusion, the ABCD approach successfully provides a strong foundation for developing creative industries based on local wisdom in this community, although further mentoring with a broader scope is recommended for more optimal outcomes